Blood-based biomarkers of inflammation in mild traumatic brain injury: A systematic review. (January 2022) - Visser, Koen; Koggel, Milou; Blaauw, Jurre; van der Horn, Harm Jan; Jacobs, Bram; van der Naalt, Joukje
Highlights: Acute interleukin 6 holds promise to establish the clinical diagnosis of mTBI. Acute interleukin 10 is a candidate marker for triaging mTBI patients for head CT. Evidence for a prognostic role of inflammatory markers in mTBI is limited. Standardization of study designs is necessary before clinical translation can occur. Abstract: VISSER, K., M. Koggel, J. Blaauw, H.J.v.d. Horn, B. Jacobs, and J.v.d. Naalt. Blood based biomarkers of inflammation in mild traumatic brain injury: A systematic review. NEUROSCI BIOBEHAV REV XX(X) XXX-XXX, 2021. – Inflammation is an important secondary physiological response to traumatic brain injury (TBI). Most of the current knowledge on this response is derived from research in moderate and severe TBI. In this systematic review we summarize the literature on clinical studies measuring blood based inflammatory markers following mild traumatic brain injury (mTBI) and identify the value of inflammatory markers as biomarkers. Twenty-three studies were included. This review suggests a distinct systemic inflammatory response following mTBI, quantifiable within 6 h up to 12 months post-injury. Interleukin-6 is the most promising biomarker for the clinical diagnosis of brain injury while interleukin-10 is a potential candidate for triaging CT scans. The diagnostic and prognostic utility of inflammatory markers may be more fully appreciated as a component of a panel of biomarkers. However, discrepancies in study design, analysis and reporting make it difficult to draw any definite conclusions. For the same reasons, a meta-analysis was not possible. We provide recommendations to follow standardized methodologies to allow for reproducibility of results in future studies.